European Academy for medicine of ageing session participants' report on malnutrition assessment and diagnostic methods; an international survey. (February 2020) - ,; ,; Andersen-Ranberg, Karen; Bonin-Guillaume, Sylvie; Conroy, Simon; Gordon, Adam; Grodziki, Tomasz; Landi, Francesco; Martínez-Velilla, Nicolás; Münzer, Thomas; Ranhoff, Anette Hylen; Roller-Wirnsberger, Regina; et al.
Summary: Introduction: Malnutrition and nutrition-related diseases are associated with hospital admissions, disability, institutionalization, and mortality in older people. Specialists in Geriatric Medicine and nutrition evaluate nutritional status as part of the comprehensive geriatric assessment; however, malnutrition still remains under-recognized and under-managed. Our survey explored nutrition assessment approaches used in daily clinical practice by geriatricians across Europe. Methods: A 19-item survey on methods and instruments for malnutrition assessment in geriatric settings, and details of any national guidelines, was sent to 40 postgraduate fellows of the European Academy of Medicine of Aging (EAMA, 2017–2019 class). Results: Thirty-six of the 40 eligible EAMA participants, representing 14 European countries, responded. In clinical practice, MNA and MNA-SF were most frequently used for screening (44.1%, 52.9%, respectively) and diagnosing (45.7%, 40.0%) malnutrition. Weight loss (n = 36, 100%), body mass index (n = 30, 85.7%), and low energy/food intake (n = 27, 77.1%) were the most frequent clinical variables considered. The absolute and relative amount of weight loss, and over what time period, varied widely. These routinely considered clinical factors contribute to validated GLIM, ASPEN-AND and ESPEN criteria for diagnosis of malnutrition, but these criteria were seldom used (GLIM = 0%, ASPEN = 0%; n = 9, ESPEN = 25.7%). National guidelines were available in 9 of the 14 countries, and generally recommended MNA and MNA-SF for community-dwelling and hospitalized older patients. Albumin was often suggested as a nutritional marker. Conclusions: Nutritional assessment is systematically performed in geriatrics; but differs widely among geriatricians and countries. Harmonizing guidelines with the new international consensus might provide best-evidence care for older people across Europe. Highlights: Nutritional assessment performed by geriatricians in clinical practice varies widely across European countries. The clinical criterion most widely used is weight loss; however, percentage weight-loss and time-frame should be evaluated to determine if re-evaluation is needed. Clinical assessment of malnutrition was based on the items that constitute the GLIM, ESPEN, and ASPEN/AND criteria, without using the three validated definitions. Harmonizing the national guidelines on malnutrition assessment with GLIM and ESPEN criteria might provide best-evidence care for older people across Europe.